Analysis OF Process Of Executing A Learning Program With A Saintific Approach At 5 Senior High School Kupang - Bana, Rifal Arma; Florentinus, Totok Sumaryanto; Haryono, Haryono (Innovative Journal of Curriculum and Educational Technology, 2021)
The study aims to analyze a partitioned learning program that includes the physical condition of the environment that supports the learning program. analyzing the availability of tools and infrastructure, human resources that endear teacher education and match education with powerful subjects that promote the implementation of the learning program. analyze the process for carrying out a saintific learning program. analyzing student learning results on cognitive, affective and psychomotor districts at 5 Senior High School kupang. The research approach used is a qualitative description approach and context-input-process-product model. The data-gathering techniques in this study use observation techniques, interviews, document studies. Studies show that the process of performing a learning program with a saintifical approach at 5 senior high school Kupang creates annual programs and semester programs first, methods used varying according to the conditions and the school environment. The school administration has hit a roadblock to the means backing out of incomplete learning. The implication is that the partition learning material must be managed properly according to the needs of learners. The implication for schools to perfect sarpras as per dictation no. 40 years 2008, so that learners can readily receive the materials presented by teachers, and in order to smooth out the scheduling learning process, teachers are more varied in using the learning methods and improving class management so that educated dean's more orderly learners are able to adopt a healthy living culture.